Graft loss attributed to possible transfusion‐transmitted ehrlichiosis following cord blood stem cell transplant. Issue 4 (7th May 2018) - Mah, Allison; Viola, George M.; Ariza Heredia, Ella; Rezvani, Katayoun; Kebriaei, Partow; Bhatti, Micah M.; Han, Xin; Shpall, Elizabeth J.; Mulanovich, Victor E.
Abstract: We present a case of possible transfusion‐transmitted Ehrlichia chaffeensis infection in a heavily transfused cord blood transplant recipient, resulting in severe infection and graft loss. Transfusion‐transmitted, vector‐borne infections in immunocompromised individuals can have severe consequences, and should be considered in hospitalized patients receiving blood products with unexplained fever or sepsis.